Micro total analysis systems 2004 : proceedings of [Mu] TAS 2004 8th International Conference on Miniaturized Systems for Chemistry and Life Sciences, Malmö, Sweden, September 26-30, 2004 /: proceedings of [Mu] TAS 2004 8th International Conference on Miniaturized Systems for Chemistry and Life Sciences, Malmö, Sweden, September 26-30, 2004. (©2004) - Unknown
No abstract available